The Tragedy of the Commons and Population Health: The State's Intervention in an Individual's Actions and Choices from a Capability Perspective. Issue 4 (2nd October 2018) - Ram-Tiktin, Efrat
Abstract: The discussion of public health ethics usually focuses on public health and relates it to the notion of a public good. In this paper, I explain why we need to focus on population health and why it corresponds to a common good and hence is prone to depletion in the absence of appropriate state regulation. Using the capability approach perspective and Sen's focus on the value of the opportunity and process aspects of freedom, I show why the state commitment to guarantee each individual the prerequisites for her positive freedom in fact justifies limiting an individual's freedom of action in order to protect the freedom of others. However, even such infringements might not suffice to maintain population health as a common good. Hence, in the third section, I look at an additional course of intervention by the state, namely the use of nudges which are intended to influence an individual's choices and to steer her to more health-enhancing behavior. In light of the possible violation of the opportunity and process aspects of individual freedom, I show why and under what circumstances the use of nudges is not only ethical, but actually preserves the two aspects of freedom and at the same time maintains the common good.